Antibacterial Effectiveness of Four Concentrations of the Hydroalcoholic Extract of Solanum tuberosum (Tocosh) against Streptococcus mutans ATCC 25175TM: A Comparative In Vitro Study - Silvana Enciso; Julia Medina; Franco Mauricio; Cesar Mauricio-Vilchez; Daniel Alvitez-Temoche; Luzmila Vilchez; Frank Mayta-Tovalino (International Journal of Dentistry)
Objective. To determine the in vitro antibacterial effect of four concentrations of the hydroalcoholic extract of Solanum tuberosum “tocosh” (HET) against Streptococcus mutans ATCC 25175TM. Methods. This was a prospective, experimental, comparative study. Fermented tocosh was subjected to hydric stress to obtain a hydroalcoholic extract at four different concentrations: 100%, 50%, 75%, and 25%. S. mutans strains were cultured in brain heart infusion agar using the swab technique. The antibacterial effectiveness of HET was evaluated following the Kirby–Bauer disk diffusion method and compared with 0.12% chlorhexidine (positive control group). Results. The highest mean inhibitory effect was achieved with HET at 100% (33.1 ± 2.2 mm, showing a gradual reduction in the other HET groups at 75%, 50%, and 25% (29.7 ± 1.3 mm, 26.6 ± 2.0, and 20.1 ± 1.8 mm, respectively)). Inferential analysis found statistically significant differences among all the experimental groups (p=0.001). The post hoc analysis also showed significant differences among all the experimental groups evaluated; however, there were no significant differences between HET 50% and chlorhexidine 0.12% (p>0.05). Conclusions. It was found that the highest antibacterial effectiveness was obtained by HET 100%, being even higher than the 0.12% chlorhexidine positive control, and was statistically significant. Post hoc analysis showed that almost all the concentrations showed optimal efficacy against S. mutans.